The medium- to long-term functional outcomes of women who have had successful anatomical closure of vesicovaginal fistulae - Mandeep Grewal; Mahreen Hussain Pakzad; Rizwan Hamid; Jeremy Louis Ockrim; Tamsin Jillian Greenwell (Urology Annals, 2019)
Context: While much has been published on vesicovaginal fistula (VVF), little is known about the urinary, bowel, and sexual functional outcomes following successful anatomical closure. Aims: We assessed the medium- to long-term urological, sexual, and bowel function outcomes following the successful anatomical closure of VVF. Patients and Methods: We conducted interviews with 36 women (median age – 47.5 years) who had successful anatomical closure of their VVF (28 vaginally and 8 abdominally) with a median of 40.5 months earlier. All completed validated questionnaires on urinary (Urogenital Distress Inventory-6 [UDI-6] and Incontinence Impact Questionnaire-7 [IIQ-7]), bowel (low anterior resection syndrome [LARS] score), and overall function (EQ5D). Sexually active patients completed the pelvic organ prolapse/ urinary incontinence sexual questionnaire (PISQ-12). All women also completed these questionnaires retrospectively for their status immediately before VVF repair. Functional outcomes were compared with preoperative function, and outcomes of those women having vaginal repair were compared with those having abdominal repair. Statistical analysis was by Student's t-test and Mann–Whitney U-test. Results: Median UDI-6 and IIQ-7 scores (low score is better) reduced significantly (P ≤ 0.01) from 16.5 and 25.5 preoperatively to 4 and 2.5 postclosure. Median LARS score was not significantly altered. Sexual function was restored in 67.6% while overall function postclosure was good (PISQ12 – low score better). Both EQ5D (low score better) and health thermometer (high score better) medians were significantly improved (P < 0.01) from 9 and 25 to 6 and 75 postclosure, respectively. There was no significant difference in the medium- to long-term outcomes of women who had had vaginal repair of their VVF and those who had had abdominal repair. Conclusions: Successful repair of VVF results in medium- to long-term significant improvement in urinary symptoms and distress, general well-being, and quality of life with no long-term adverse effects on bowel function regardless of route of repair. Sexual function is restored in 67.6%.